(untitled) (Journal of Universal Excellence, 2026)
Research Question: In the research, with the help of selected articles, we asked a research question, how to create and upgrade a sustainable future in organisation Purpose: Teoretical presentation of the EFQM Bussines Excellence Model and self-assessment emphasis on Creating sustainable future of importance for leaders of organisations and presentation of environmental, social and economic effects. Method: In the research, we used a qualitative method based on analythical study. We collected litherature, articles, and information and reviewed and analyzed them. Results: The research found that creating a sustainable future requires an equal emphasis on the social, enviroment and economy, and the key is the support of top management, which leads to the business excellence of the organization. Organization: Research and study of various articles gives us information about the inportance of leaders in the organization and strategic orientation towards a sustainable future. Society: The organization is the one that can do the most for the social environment and its competitive and economic advantage through its activities for a sustainable future. Originality: The research includes three factors that, with the help of leaders and stakeholders, lead to a sustainable future. Limitations/Future Research: The research was conducted on the basis of collected literature, articles and information.